Climate-Smart Mapping and Adaptation Planning (CS-MAP) of 12 provinces in Vietnam’s Red River Delta and Northern Midlands - CGIAR Research Program on Climate Change, Agriculture and Food Security; Alliance of Bioversity International and CIAT; Department of Crop Production; Institute of Water Resources Planning, Vietnam (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
To address the water management crisis in Red River Delta and Northern Midlands, the Department of Crop Production, together with CCAFS SEA and Alliance of Bioversity International and CIAT, tapped the Institute of Water Resources Planning to implement Climate-Smart Mapping and Adaptation Planning (CS-MAP) in all 10 provinces of Red River Delta. Because they are an integral part of the watershed system in the region, two provinces of the Northern Midlands and Mountainous region, specifically Bac Giang and Phu Tho, were also included in the CS-MAP project. Using the CS-MAP methodology, the research team developed the maps on: water shortage risk, winter-spring rice cultivation schedule, and areas that need to change crop structure in winter-spring cropping to adapt to the water shortage situation.